MODEL PEMBELAJARAN REACT UNTUK MATA PELAJARAN IPA - Hakim, Mukhammad Luqman (Institut Agama Islam Negeri Kediri, 2017)
Abstract: Instructional model REACT, which is a learning method that relates the lesson taught to the student's daily life, as well as trains them to work in groups to exchange their knowledge. The objective of this study is to examine the effect of contextual learning method model REACT on the science learning outcomes. This research is a part of a quasi-experimental research. The result of learning outcomes analysis of the experimental class and the control class showed that the score of tcount was 5.213 and the probability was 0.000. Because the probability score showed 0.000 less than 0.005, then H0 was rejected. So, it could be concluded that there were significant differences between the learning achievement of the control class and the experiment one. It was known tcount score was 5.213 while ttable was 1.691. Then, based on this data, the t-test was carried out in two sides with the accepted H0 between (-1.691) and (1.691). Based on these results, it can be concluded that the hypothesis (H0) which states